Design and Implementation of custom Point of Sales using Waterfall Method for Corner Shop 70 - Yovita Chandra, Kezia; Tanamal, Rinabi (Teknik Informatika Universitas Pamulang, 2024)
With globalization, technological growth in various parts of the world is rushing. Likewise, every year, the use of ICT always increases in Indonesia. We can feel the world starting to digitalize every aspect of people's lives, such as education, health, etc. Digitalization in business sectors helps minimize problems experienced mainly by small and micro-scale, such as stock-opname errors. The same situation occurred in one of the micro-businesses, Toko Pojok 70, which runs the business process manually. This research is conducted due to unintegrated data and complicated stock recording processes. The owner tends to lose the item, and sometimes miscalculates the total transaction which leads to business loss. The solution to the owners’ problem is by technology known as point of sales (POS). By adopting the Waterfall method business owners can determine what features on POS are needed to adopt their business processes which involve managing goods, reporting, transactions, and return processes also may help run business processes faster, more precisely, and organized. Based on the requirement analysis, implementation, and testing result. The point of sales that has been created can be implemented on Toko Pojok 70 to handle the problems that occurred in the business.